Інвазійні комахи-шкідники інтродукованих рослин дендрологічного парку “Олександрія” НАН України. Повідомлення 3: щодо біології Pineus orientalis (Dreyfus, 1889) (Heteroptera: Adelgidae) - Dragan, Grygoriy (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2026)
The article discusses problems associated with the introduction of plants and the accompanying invasion of new species of insect pests into park plantings. It emphasises the urgent need to study their biology. The paper describes some biological features of one of the invasive species of pests – the Eastern pine adelgid, Pineus orientalis. The data on phenology, feeding and reproductive features, number of generations, composition of life cycle morphs, and damage caused by P. orientalis to its forage plants are presented.